Creating a sustainable action-oriented engagement infrastructure—a UMN-MIDB perspective - Randolph, Anita C.; Henry, Alex; Hewitt, Amy; Mejia, Angie P.; Sethuraju, Raj; DeJoseph, Meriah; Koenig, Melissa; Elison, Jed T.; Fair, Damien A. (Frontiers in Integrative Neuroscience, 2022)
Following the murder of George Floyd on May 25, 2020, Minneapolis represented the epicenter of protests that would reverberate internationally and re-instantiate a reckoning of the systemic and institutional racism that plagues American society. Also in the summer of 2020, and after several years of planning, the University of Minnesota (UMN) launched the Masonic Institute for the Developing Brain (MIDB), an interdisciplinary clinical and community research enterprise designed to create knowledge and engage all members of our community. In what follows, we describe the mission of the MIDB Community Engagement and Education (CEEd) Core and adjacent efforts within the UMN neuroscience and psychology community. Inherent to these efforts is the explicit attempt to de-center the dominant academic voice and affirm knowledge creation is augmented by diverse voices within and outside of traditional academic institutions. We describe several initiatives, including the Neuroscience Opportunities for Discovery and Equity (NODE) network, the NextGen Psych Scholars Program (NPSP), the Young Scientist Program, among others as exemplars of our approach. Developing and fortifying sustainable pathways for authentic community-academic partnerships are of central importance to enhance mutually beneficial scientific discovery. We posit that traditional academic approaches to community engagement to benefit the institution are severely constrained and perpetuate inherently exploitative power dynamics between academic institutions and communities.